Efficacy and safety of acupuncture in post-stroke constipation: a systematic review and meta-analysis - Sun, Tianye; Wang, Kaiyue; Li, Lili; Yan, Mingyuan; Zou, Lin; Zhang, Mi; Yang, Songyi; Wu, Jing; Liu, Jinmin (Frontiers in Neuroscience, 2023)
Objective: This study aims to evaluate the efficacy and safety of acupuncture in the treatment of PSC. Methods: A systematic search of eight databases was conducted to identify PSC-related randomized clinical trials from the inception of each database through May 2023. Methodological quality assessment was conducted by RoB 2.0, meta-analysis was conducted by RevMan 5.3 and Stata 15.1, and evidence quality was evaluated by GRADE. Moreover, reporting quality of acupuncture interventions was assessed using the STRICTA. Results: Thirty RCTs involving 2,220 patients were identified. We found that acupuncture was superior to conventional treatment (CT) in improving total responder rate [risk ratio (RR): 1.16, 95% confidence interval (CI): 1.09 to 1.25, p < 0.0001], decreasing constipation symptom scores [standardized mean difference (SMD): -0.65, 95% CI: -0.83 to -0.46, p < 0.00001], increasing serum SP levels (SMD: 1.92, 95% CI: 0.47 to 3.36, p = 0.009), reducing the time to first bowel movement (BM) (SMD: -1.19, 95% CI: -2.13 to -0.25, p = 0.01), and lowing serum VIP levels (SMD: -2.11, 95% CI: -3.83 to -0.38, p = 0.02). Furthermore, acupuncture plus CT was superior regarding total responder rate (RR: 1.26, 95% CI: 1.17 to 1.35, p < 0.00001), serum SP levels (SMD: 2.00, 95% CI: 1.65 to 2.35, p < 0.00001), time to first BM (SMD: -2.08, 95% CI: -2.44 to -1.71, p < 0.00001), and serum VIP levels (SMD: -1.71, 95% CI: -2.24 to -1.18, p < 0.00001). However, regarding Bristol Stool Scale (BSS) score, acupuncture plus CT was superior to CT (SMD: -2.48, 95% CI: -3.22 to -1.73, p < 0.00001), while there was no statistically significant difference between acupuncture and CT (SMD: 0.28, 95% CI: -0.02 to 0.58, p = 0.07). Acupuncture causes fewer AEs than CT (RR: 0.13, 95% CI: 0.06 to 0.26, p < 0.00001), though there was no statistically significant difference between acupuncture plus CT vs. CT (RR: 1.30, 95% CI: 0.60 to 2.84, p = 0.51). Conclusions: Acupuncture may be an effective and safe therapy for PSC. However, given the inferior quality of clinical data, additional well-designed RCTs are required to confirm these findings.